Application of nanostructures in diagnosis and therapy of cervical cancer: A review study - Kiana Ketabi; Aida Gholoobi; Zahra Meshkat (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2017)
Introduction: Cancer is one of the major health problems throughout the world. Among these, cervical cancer is the second most common cancer among women in the world. About 80% of new cases of cervical cancer occur in developing countries. Regarding to the problems in diagnosis and treatment of this cancer during past two decades, molecular drugs have helped to the diagnosis and treatment of different kinds of cancers, including cervical cancer. In this regard, we can name a variety of multifunctional nanostructures. The present review study was performed with aim to introduce and evaluate some of the current nanostructures developed for this purpose. Methods: The key words of diagnostic nanoparticles, therapeutic nanoparticles, organic nanoparticles, inorganic nanoparticles and cervical cancer which were selected from Mesh were searched in scientific databases such as ISI, Pub Med, Google scholar and Scopus with no time limitation. The articles' entering to this review study was based on using the nanostructures in diagnosis or treatment of cervical cancer. At the end, input data were qualitatively analyzed. Results: By reviewing several articles and according to the studies' results, it was found that nanoparticles can generally be one of the proper candidates for diagnosis and treatment of cervical cancer. Among these nanostructures, iron oxide nanoparticle had the greatest apply in diagnosis of this cancer that due to its super-paramagnetic property, had provided the possibility of non-invasive MRI imaging for patients. For treatment of cervical cancer, routine drugs along with suitable nanostructures such as PLGA to target and accumulate drugs to the target tissue have been used. Conclusion: In general, superparamagnetic iron oxide nanoparticles and Au/Ag core-shell nanoparticles can be a good candidate for the diagnosis and treatment of cervical cancer. Also, among the organic nanoparticles, PLGA nanoparticles had the greatest apply in the delivery of drugs to the target tissue of cervical cancer.